Perinatal outcomes after maternal 2009/H1N1 infection: National cohort study - Pierce, M; Kurinczuk, J; Spark, P; Brocklehurst, P; Knight, M (2011)
Objectives: To follow up a UK national cohort of women admitted to hospital with confirmed 2009/H1N1 influenza in pregnancy in order to obtain a complete picture of pregnancy outcomes and estimate the risks of adverse fetal and infant outcomes. Design: National cohort study. Setting: 221 hospitals with obstetrician led maternity units in the UK. Participants: 256 women admitted to hospital with confirmed 2009/H1N1 in pregnancy during the second wave of pandemic infection between September 2009 and January 2010; 1220 pregnant women for comparison. Main outcome measures: Rates of stillbirth, perinatal mortality, and neonatal mortality; odds ratios for infected versus comparison women. Results: Perinatal mortality was higher in infants born to infected women (10 deaths among 256 infants; rate 39 (95% confidence interval 19 to 71) per 1000 total births) than in infants of uninfectedwomen (9 deaths among 1233 infants; rate 7 (3 to 13) per 1000 total births) (P<0.001). This was principally explained by an increase in the rate of stillbirth (27 per 1000 total births v 6 per 1000 total births; P=0.001). Infants of infected women were also more likely to be born prematurely than were infants of comparison women (adjusted odds ratio 4.0, 95% confidence interval 2.7 to 5.9). Infected women who delivered preterm were more likely to be infected in their third trimester (P=0.046), to have been admitted to an intensive care unit (P<0.001), and to have a secondary pneumonia (P=0.001) than were those who delivered at term. Conclusions: This study suggests an increase in the risk of poor outcomes of pregnancy in women infected with 2009/H1N1, which reinforces the message from studies of maternal risk alone. The health of pregnant women is an important public health priority in future waves of this and other influenza pandemics.